Design of Wireless Sensor Network (WSN) with RF Module for Smart Irrigation System in Large - Radi; Murtiningrum; Purwantana, Bambang; Muzdrikah, Fajar Siti; Nuha, M. Shohibun; Rivai, Muhammad (2018 International Conference on Computer Engineering, Network and Intelligent Multimedia (CENIM), 2018)
Give water to cropsthat is usually called as irrigation is one of the most important activities in farming system. Because water determine the crops growth and development, it should be available sufficiently inside the planting media. Recently, such control technology for crops irrigation has been developed though its application for such drip irrigation is still limited in small cultivated area. For extensive crop cultivation areas such as plantations, it needs a strategy to apply the technology in large cultivated area. We propose a model that is called as a smart irrigation systems (SIS). In the model, the large cultivated area is divided into several plots, where each plot has an independently automatic irrigation system. In order to be easily managed, each irrigation system in each plot can communicate to others and all information should be collected in a data server that is connected to cloud system. Since that common plantation area has limitation of communication lines, we propose a wireless sensor network (WSN) based on a radio frequency (RF) communication to connect all automatic irrigation systems. This paper focuses on designing a WSN prototype based on a radio frequency (RF) module to develop a smart drip irrigation system for large cultivated land. The WSN is designed from a master node functioned as coordinator and three slave nodes. The master and slave nodes are equipped with an RF module with a 2.4GHz frequency for communication. After construction, the WSN prototype with star topology is then tested for its ability, especially for transmitting data from slave to master and vice versa. The prototype has been tested with varied distance of 50 m, 100 m and 150 m between master and slave in a tree-blocked open space. Based on the data losses, the prototype has a good performance if the distances is less than 100 m.